Toxic epidemic necrolysis unleashed by the use of ibuprophen in a patient with rheumatoid art - case report (Research, Society and Development, 2020)
Toxic epidermal necrolysis (NET) is characterized by a generalized mucocutaneous eruption with extensive blisters and areas of epidermal necrosis, resembling the appearance of a large burn. Body surface involvement is greater than 30% in NET. In addition, it is a rare condition with an annual incidence of 0.4 to 1.45 per million. Drugs are the main etiological agents of SSJ and NET, being responsible for 80% to 95% of cases. Ibuprofen is a non-steroidal anti-inflammatory drug (NSAID) widely used in our country and is a therapeutic option for rheumatoid arthritis. The most frequent complications of NET are eyepieces, sepsis, keratoconjunctivitis, hyper and hypopigmentation of the skin. The treatment of this condition involves immediate suspension of the suspected drug, general care and support measures, since there is no specific treatment. The present work is a case report, with a qualitative approach and with descriptive purposes. In order to explain the case of a patient who used sporadic ibuprofen due to the newly diagnosed rheumatoid arthritis and triggered an episode of NET, appropriate treatments were performed with a favorable outcome. We conclude that because NET is a serious disease with high morbidity and mortality, it must be quickly diagnosed, treated appropriately and with intense surveillance.